The Urgency of Karyotyping Examination in Male Infertility Patients with Primary Hypogonadism - Putu Dyah Agustina Lestari; I Gusti Ngurah Pramesemara (Universitas Airlangga, 2023)
Infertility is a failure to get pregnant after one year of sexual intercourse without using contraception. The causes of infertility, especially in men, are very complex, including the aging process, hormonal disorders, lifestyle, environment, metabolic disease, and genetic problems. One of the most difficult causes in male infertility is genetic problems. In this case, a 35 year old man was reported with primary infertility and often experienced premature ejaculation and even anejaculation. Previously, the patient had repeatedly consulted about his condition at other fertility service centers. The conclusion obtained was that the patient had azoospermia with bilateral varicoceles and had been given hormone therapy but had not yet found a final diagnosis so the patient was still confused about what had happened to him. At the first visit the patient underwent a sperm analysis and the results were azoospermia. Then, based on the results of the history and physical examination, which indicated hypogonadism, a Y chromosome microdeletion examination was carried out, and a deletion was found in the AZFc region, which is a marker of infertility that causes spermatogenic failure. The examination was continued with karyotyping, the result was 47.XXY, consistent with the condition of Klinefelter syndrome. Conclusion: Carry out a karyotyping examination if you find signs and symptoms that suggest primary hypogonadism in male infertility. This can be done to streamline the diagnostic approach time in patients with primary hypogonadism, especially those with infertility.